Discourse analysis of purpose, structure and epistemological assumptions within Distinction Level postgraduate studient texts from Apprenticeship genres within three related disciplines. - Findlay, Benjamin (2015)
There are about 200,000 non-native English language students studying at postgraduate level in English in the UK. Many of these students take English for Academic Purposes (EAP) classes either before or during their studies in order to assist with language difficulties. Two aspects of this are developing appropriate discourse competence and gaining an understanding of the genres they must use on their courses. Being able achieve these involves being able to understand the purpose, structure and underlying epistemology of the texts they are expected to write. The extent to which these features are similar across and within target disciplines affects practical considerations of EAP class groupings and syllabus design. This paper investigates distinction level student papers from the ‘apprenticeship’ genre family in three related disciplines in order to investigate these features. The related genres are Hospitality, Leisure and Tourism Management, Business and ‘soft’ (Biglan, 1973) Engineering. Results show that there is significant diversity and difference within the texts. This is seen both within and between disciplines. This finding has implications for how these discourses should be taught on postgraduate EAP courses.